Female patients display poorer burn-specific quality of life 12 months after a burn injury. Issue 1 (January 2017) - Wasiak, J.; Lee, S.J.; Paul, E.; Shen, A.; Tan, H.; Cleland, H.; Gabbe, B.
Abstract: Introduction: Although gender differences in morbidity and mortality have been measured in patients with moderate to severe burn injury, little attention has been directed at gender effects on health-related quality of life (HRQoL) following burn injury. The current study was therefore conducted to prospectively measure changes in HRQoL for males and females in a sample of burn patients. Methods: A total of 114 adults who received treatment at a statewide burns service for a sustained burns injury participated in this study. Instruments measuring generic health status (Short Form 36 Medical Outcomes Survey version 2), burn-specific HRQoL (Burns Specific Health Scale-Brief), psychological distress (Kessler Psychological Distress Scale) and alcohol use (Alcohol Use Disorders Identification Tool) were prospectively measured at 3, 6 and 12 months post-burn. Results: In the 12 months post-injury, female patients showed overall poorer physical ( p = 0.01) and mental health status ( p < 0.001), greater psychological distress ( p < 0.001), and greater difficulty with aspects of burn-specific HRQoL: body image ( p < 0.001), affect ( p < 0.001), interpersonal functioning ( p = 0.005), heat sensitivity ( p = 0.01) and treatment regime ( p = 0.01). While significant interaction effects suggested that female patients had more improvement in difficulties with treatment regime ( p = 0.007), female patients continued to report greater difficulty with multiple aspects of physical and psychosocial health status 12 months post-injury. Conclusion: Even though demographic variables, injury characteristics and burn care interventions were similar across genders, following burn injury female patients reported greater impairments in generic and burn-specific HRQoL along with psychological morbidity, when compared to male patients. Urgent clinical and research attention utilising an evidence-based research framework, which incorporates the use of larger sample sizes, the use of validated instruments to measure appropriate outcomes, and a commitment to monitoring long-term care, can only improve burn-care.